2022
DOI: 10.3390/cancers14174148
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Surgical Techniques in Patients with Rectal Cancer on Spine Mobility and Abdominal Muscle Strength—A Prospective Study

Abstract: The aim of this non-randomized study was to evaluate the impact of spine joint mobility and chest mobility on inhalation and exhalation, and to assess the abdominal muscle strength in patients undergoing surgery for colorectal cancer with one of the following methods: anterior resection, laparoscopic anterior resection or abdominoperineal resection. In patients who were successively admitted to the Department of Surgical Oncology at the Oncology Center in Bydgoszcz, the impact of spine joint mobility, muscle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…An increase in moderate to vigorous activity after CRC surgery is associated with enhanced recovery of physical functioning, and is observed regardless of physical activity level before the surgery (van Zutphen et al, 2017). After surgery, core muscle stabilisation is necessary because the strength of the abdomen and spine is weakened (Glowacka-Mrotek et al, 2022) and hernia is a frequent negative outcome after CRC surgery (Karlsson et al, 2021). One study showed that when people after CRC engage in training that supports the core muscles, it improves musculoskeletal conditions, specifically those related to pain and internal oblique thickness (Cantarero-Villanueva et al, 2017).…”
Section: Physical Activity Changementioning
confidence: 99%
“…An increase in moderate to vigorous activity after CRC surgery is associated with enhanced recovery of physical functioning, and is observed regardless of physical activity level before the surgery (van Zutphen et al, 2017). After surgery, core muscle stabilisation is necessary because the strength of the abdomen and spine is weakened (Glowacka-Mrotek et al, 2022) and hernia is a frequent negative outcome after CRC surgery (Karlsson et al, 2021). One study showed that when people after CRC engage in training that supports the core muscles, it improves musculoskeletal conditions, specifically those related to pain and internal oblique thickness (Cantarero-Villanueva et al, 2017).…”
Section: Physical Activity Changementioning
confidence: 99%